Pemutakhiran Dokumen Profil Desa Untuk Basis Data Pembangunan Desa Patikalain Kecamatan Hantakan Kabupaten Hulu Sungai Tengah - Zulhidan, Muhammad Royyan; Khairussalam; Zhafirah, Haura; Asrariah, Siti; Adnyana, I Kadek Ukir Dwi; Tasti, Adinda Nur; Nabilah, Yashna; Enjella, Nadia; Khairunnisa, Syifa; Fahma, Erisa Nur; Risna; Kimil, Muhammad Rezky (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
The existence of a village profile is vital, because it provides a comprehensive picture of the character of the village which includes basic family data, the potential of natural resources (SDA) and human resources (HR), institutions, facilities and infrastructure, as well as the development of progress and problems faced by the village. The Patikalain Village profile updating program carried out by the service team was carried out to provide comprehensive and accurate data to support more effective planning and implementation of development programs, understand community needs, and increase the participation and welfare of village communities. The parties involved in the process of updating the village profile include the village government, and the village community itself who play a role in data collection and information validation. In carrying out this village profile updating program, the service team applies the live-in method, meaning that the service team lives permanently at the location of program implementation from July to September 2024 in Patikalain Village, Hantakan District, Hulu Sungai Tengah Regency. The activities carried out to support the Patikalin Village profile updating program include: 1) Recruitment of village youth as prospective pioneers; 2) Training of prospective pioneers to become drivers of village development; 3) Designing data requirements instruments; 4) Participatory household census; 5) Data analysis and compilation; 6) Compilation of village profile documents. A more structured and accurate profile of Patikalain Village, covering various important aspects that were previously not well-documented, can be a strong foothold for more targeted, effective, and sustainable development planning, and can improve the overall welfare of the village community.